Effects of Some Growth Factors and Cytokines on the Expression of the Repair Enzyme MGMT and Protein MARP in Human Cells In Vitro : Effect of Some Growth Factors and Cytokines - Kotsarenko, Kateryna; Lylo, Valentyna; Ruban, Tetiana; Macewicz, Larysa; Lukash, Lyubov (Biochemical genetics, 2018)
The inducible repair enzyme O6-methylguanine-DNA methyltransferase (MGMT) eliminates O6-methylguanine adducts in DNA and protects the cells from damaging effects of alkylating agents. We have found that anti-MGMT antibodies recognize both the MGMT protein with a mol. weight ~ 24 kDa and a protein with a mol. weight ~ 48 kDa, which was named MARP (anti-methyltransferase antibody recognizable protein). A number of growth factors and cytokines were shown to regulate the expression of MGMT and MARP proteins. The ranges of concentrations of several growth factors and cytokines that caused increasing or decreasing protein amounts in human cell cultures were determined. The results of special biological experiments have allowed us to assume a possible role of MARP in the repair of alkyl adducts in human cells.
Keywords: DNA modifikační methylasy; mezibuněčné signální peptidy a proteiny; Hep G2 Cells; buněčné linie; Cytokines; buňky Hep G2; Intercellular Signaling Peptides and Proteins; nádorové supresorové proteiny; In Vitro Techniques; cytokiny; techniky in vitro; lidé; enzymy opravy DNA; DNA Repair Enzymes; Cell Line; regulace genové exprese; Tumor Suppressor Proteins; buněčné kultury; Gene Expression Regulation; Cell Culture Techniques; DNA Modification Methylases; Humans